Manajemen Bencana Dalam Penanganan Pasca Bencana BPBD Kabupaten Aceh Barat - Selvia Rahmah; Ikhsan Ikhsan (Journal of Social Politics and Governance (JSPG), 2022)
This study aims to see how the post-disaster management carried out by the BPBD of West Aceh Regency in post-disaster handling. This study uses a qualitative method with a case study approach. The theory used about disaster management, there are 3 stages with indicators of post-disaster rehabilitation and reconstruction coverage, namely (1) Pre-Disaster, (2) During the Event, and (3) Post-Disaster. The results indicate that the Disaster Management of West Aceh District BPBD in Post-Disaster Handling has generally been carried out well. This rehabilitation and reconstruction process was carried out according to data sources from informants who worked at the BPBD of West Aceh Regency from 2017 to 2021. In 2022, the rehabilitation and reconstruction process is not carried out because considering the disaster that occurred in this year there is no need for a rehabilitation process and also budget problems which are obstacles in carrying out the post-disaster management process.